Survival and longevity among male Australian elite athletes: A retrospective cohort study - Lystad, R. P.; Vedantam, S. (Journal of Science and Medicine in Sport, 2025)
Objectives To quantify and compare survival and longevity in three populations of male Australian elite athletes, relative to sex- and age-matched referents from the general population.